KEPEMIMPINAN KEPALA SEKOLAH DI SEKOLAH BERSTANDAR NASIONAL (Studi Situs SMP Negeri 20 Purworejo) - KRISTIAJI , SUWASONO (2011)
The objectives of this research are (1) to describe the principal leadership of national standard school in improving academic quality at State Junior High School 20 Purworejo. (2) to describe the principal leadership of national standard school in improving non-academic quality at State Junior High School 20 Purworejo. This research is qualitative conducted at State Junior High School 20 Purworejo. The main subject of this research is principal and vice principal. Technique of collecting data used in this research is observation, interviews, and documentation. Technique of data analysis in this research used analysis model namely data collection, data reduction, presentation and conclusion. Data validity in this research includes credibility, transferability, dependability, and confermability. The results of this research are (1) the pattern of principal leadership in improving academic quality conducted with (a) delegate, cooperative, and participatory; (b) the preparation of activities plan that will be conducted by the school in the form of short plan, medium or long term plan; (c) utilizing of education resources both from educator and administrator of education; (d) conduct open management to where the principal conducts cooperation with all schools' member in managing the school and improving the teachers' competence through MGMP activities, workshop, seminar, or training. The principal always gives reward to students that have achievement; (2) the principal do some steps to improve non-academic quality includes (a) asks the school committee to prepare the school program together; (b) non-academic program contains extracurricular activities held by school and for school committee gives financial support; (d) facilitate the infrastructure fund that support non-academic quality; (e) improving the motivation by giving reward to teacher that have achievement in non- academic field; (f) increasing the role and support of society to develop the school.